Reflections and questions about the clinical tools and the setting of psychological intervention used in presence of disability - Vari, Roberto (Quaderni di Psicologia Clinica, 2014)
The article analyses the issue of the different types of setting and of the clinical tools available to the psychologist in his/her intervention. It is assumed that the non interpretative interventions, although widely employed in the clinical practice, have not found a suitable theoretical and methodological systematization. The article reports and comments the way different types of setting and of operative tools have been set in four brief clinical episodes occurred in a mental health centre. Further on are presented enquiries and reflections about the criteria presiding over the modulation of the different clinical tools throughout the intervention. The tools of the intervention, including the interpretation, are referred to as the psychologist’s relational proposals aiming at the achievement of the objectives. In the absence of a unifying theory of the technique, the considerable variety and the enhancement of the clinical tools available, expose to risk of fragmentary and methodologically incoherent praxsis. It is argued that the creative exploration of new tools in the clinical field, starting from the critical analysis of the individualist paradigm, enhances the potentiality of the psychological intervention and contributes to the reflection on the theoretical-methodological constructs including those inherent the classical dual setting.